2017
DOI: 10.1002/cb.1672
|View full text |Cite
|
Sign up to set email alerts
|

“A few bad apples” or “rotten to the core”: Perceptions of corporate culture drive brand engagement after corporate scandal

Abstract: Following unethical corporate behavior, consumers face decisions on how to engage with brands in the future. Consumers' beliefs about the underlying causes of a corporate scandal may influence future patronage intentions, for example, by influencing perceived likelihood of future wrongdoing. We investigated how beliefs about corporate culture and consumer proximity to the recent Volkswagen diesel emissions scandal influence expectations of future ethical action by Volkswagen Group (VW), feelings of anger, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 68 publications
2
33
1
5
Order By: Relevance
“…A greater proximity raises the moral relevance of a problem and, subsequently, the obligation to act. Guckian, Chapman, Lickel, and Markowitz (2018) and Puncheva-Michelotti, Hudson, and Michelotti (2018), based on this, suggest that a greater sense of closeness with a victim of socially irresponsible behavior fosters the perception of moral duty of the company and affects commitment to the brand. Mencl and May (2008) identified three nonexclusive dimensions of proximity: physical, social, and psychological.…”
Section: The Influence Of Beneficiary Proximity On Csr Effectivenessmentioning
confidence: 96%
“…A greater proximity raises the moral relevance of a problem and, subsequently, the obligation to act. Guckian, Chapman, Lickel, and Markowitz (2018) and Puncheva-Michelotti, Hudson, and Michelotti (2018), based on this, suggest that a greater sense of closeness with a victim of socially irresponsible behavior fosters the perception of moral duty of the company and affects commitment to the brand. Mencl and May (2008) identified three nonexclusive dimensions of proximity: physical, social, and psychological.…”
Section: The Influence Of Beneficiary Proximity On Csr Effectivenessmentioning
confidence: 96%
“…Across multiple domains, research has identified a variety of factors that drive consumers' post-scandal purchase intentions, including corporate social responsibility evaluations (Klein & Dawar, 2004;Russell, Russell, & Honea, 2016), preexisting brand relationships (Dawar & Pillutla, 2000;Grégoire & Fisher, 2008;Grégoire, Tripp, & Legoux, 2009), attributions of blame (e.g., Folkes, 1988;Guckian et al, 2018;Lei, Dawar, & Gürhan-Canli, 2012), proximity to the scandal (e.g., Guckian et al, 2018;Johnson, Matear, & Thomson, 2010), and moral self-conscious emotions Guckian et al, 2018;. Extant research in this domain has largely relied on the use of vignettes and/or stimulus narratives-based in part on prior instances of wrongdoing-to examine the nature of the relationship between corporate wrongdoing and consumer reactions (Grappi et al, 2013).…”
Section: Consumer Reactions To Corporate Wrongdoingmentioning
confidence: 99%
“…How a given instance of corporate wrongdoing is both presented to (e.g., via media coverage) and perceived by consumers is important because ascriptions of responsibility and blame influence consumers' reactions to incidences of corporate wrongdoing (e.g., Folkes, 1988;Guckian, Chapman, Lickel, & Markowitz, 2018). When consumers come to view a few bad actors as primarily responsible for a scandal, they are often quick to absolve the larger corporation of responsibility, which in turn suppresses motivation to meaningfully punish the organization through, e.g., consumer actions (e.g., boycotting); in contrast, when people harbor the belief that corporate scandals are a by-product of a corrupt corporate culture, they are more likely to respond negatively toward the brand (e.g., show increased levels of anger, decreased patronage intentions; Guckian et al, 2018). However, it remains unclear whether people's mental models of blame and responsibility in the context of organizational wrongdoing consistently and predictably influence their reactions to diverse real-world corporate scandals, as past work has generally focused only on single instances of wrongdoing (e.g., Volkswagen diesel emissions scandal).…”
mentioning
confidence: 99%
“…Es por esto que la conducta de las marcas es un aspecto relevante para estimular compromiso en sus clientes, comportamiento que perfila la relación de la organización con la sociedad en general (Wong & Merrilees, 2015), sin embargo, en muchos casos, la estrategia de compromiso con públicos de interés se ha presentado desde una aproximación superficial, relacionada con la construcción de reputación corporativa, con lo cual se eluden asuntos que interesan de manera sensible a dichos públicos y se evita un real compromiso con estos de forma bidireccional (Biraghi et al, 2017). Guckian et al (2018) señalan que, al presentarse un escándalo que pone en entredicho la reputación de una organización, cuando los clientes perciben que este se debió a acciones individuales y no como consecuencia de la cultura corporativa, se presentan más expectativas de que dicha empresa se comporte de forma ética en el futuro, menos enojo ante los perjuicios ocasionados y mayores intenciones de compromiso en adelante con la entidad. Es por esto que la interacción y las relaciones cercanas son factores clave para desarrollar conductas de compromiso en los consumidores, quienes se involucran con las marcas a partir de su comportamiento y de sus acciones de mercadeo, en este sentido, si en el marketing de compromiso se concibe al cliente como una especie de responsable de mercadeo, entonces la empresa debería configurarse como un pseudoempleador, que incentiva el trabajo y la productividad del cliente, traduciéndolo en iniciativas de compromiso efectivas (Harmeling et al, 2017), de esta forma, la innovación exitosa del servicio depende también de prácticas novedosas para motivar la participación del cliente y promover su lealtad (Leckie et al, 2017), por lo cual, los objetivos que buscan las empresas, al propiciar compromiso por parte de sus clientes, se relacionan con contribuciones directas como son las compras, así como con otras de tipo indirecto como la recomendación de los productos o servicios que respalda la marca y comportamientos interactivos con la compañía (Bleier et al, 2017).…”
Section: Compromiso Del Consumidor/cliente Con Marcas U Organizacionesunclassified